Wake up to a world in communication - Agravante, Josefina Angeles 1943-.; Buenaventura, Villy; University of the Philippines. Open University ([Quezon City] U.P. Open University, 2005)
A lecture on communication.
Published jointly with the Commission on Higher Education.
Title on disc: Wake up to a world of communication.
Executive producer: Maria Lurenda Suplido ; Assistant director: Arminda V. Santiago ; Associate producers: Mitzi Rivera and Robert Ryan B. Banzuela ; Scriptwriters: Josefina Agravante, Villy Buenaventura and Grace Javier Alfonso.
Narrators: Josefina Agravante and Villy Buenaventura.
Keywords: Communication; Communication models; Interpersonal communication; Communication -- Psychological aspects